Evasão na educação superior a distância: estudo de caso no Instituto UFC Virtual - Oliveira Sobrinho, José Ferreira de (2013)
Since the mid - 1990s, there is an expansion of the supply of Distance Education in Brazilian higher education. This expansion responds on the one hand, the demands of the world of work aimed at training professionals able to ensure the competitiveness of organizations in the economic globalization scenario and on the other, the educational policies to expand the supply of vacancies in teaching graduation. In speeches defending the EAD in higher education, the relationship has been highlighted this educational mode with the possibility of educational inclusion and teacher education. In Brazil, the gross enrollment ratio in higher education is still one of the lowest in Latin America, although since the 1960s the federal government policy for the sector has been to increase enrollment via privatization and more recently with the creation the Open University System of Brazil (UAB). The UAB had its inception in the year 2005 to provide access to part of the population working and has no way to attend classroom learning and has prioritized the training of educators, by encouraging the articulation and integration of a national system higher education, formed by public institutions of higher education, in partnership with states and municipalities, using distance education for the placement of the contents of the various courses. Analyzing the census conducted by the Brazilian Higher Education INEP, it was found that the rate of growth in enrollment in higher education distance was stronger than classroom courses. In 2012, enrollment in distance education courses increased by 12.2 %, while in attendance, 3.1%. However, 84.2 % of students enrolled in higher education continue in the face classrooms. Only 15.8% are enrolled in distance learning courses. Circumvention is one of the issues that concern managers of higher education institutions. Thus, this study sought to identify the determinants of evasion in undergraduate courses offered by the UFC - Virtual Institute (Virtual Institute of the University of Ceará). It is an exploratory and descriptive research and uses bibliographic, documentary and survey procedures in a qualitative and quantitative approach. To identify factors evasion, 91 questionnaires to 69 students and dropouts to - face support tutors were applied. In data analysis, the most recurrent factor in the students' opinion was related to teachers and tutors (75.82%) difficulty, and in the opinion of the tutors was poor virtual environment (89.85 %). Next are the personal problems which had an incidence of (62.62 %) and (85.51 %) of the tutors mentioned issues related to poor performance of the managers, teachers and tutors. Among the least recurring factors are: lack of base in high school, the difficulty to use the computer, the installation and maintenance of the poles. For the data analysis, it is noticed that the model adopted by EAD Brazilian public universities does not offer the student the flexibility he expected.